(untitled) (The Conference Hub, 2025)
This article examines the impact of communication on students in primary education. Communication supports not only learning but also the social, emotional and psychological development of students. The article highlights the role of effective communication between teachers and students in developing self-awareness and communication skills. It also highlights the impact of communication on student relationships and its importance in achieving academic success.